Is there a gap between recommended and 'real world' practice in the management of depression in young people? A medical file audit of practice - Hetrick Sarah E; Thompson Andrew; Yuen Kally; Finch Sue; Parker Alexandra G (BMC, 2012)
Abstract Background Literature has shown that dissemination of guidelines alone is insufficient to ensure that guideline recommendations are incorporated into every day clinical practice. Methods We aimed to investigate the gaps between guideline recommendations and clinical practice in the management of young people with depression by undertaking an audit of medical files in a catchment area public mental health service for 15 to 25 year olds in Melbourne, Australia. Results The results showed that the assessment and recording of depression severity to ensure appropriate treatment planning was not systematic nor consistent; that the majority of young people (74.5%) were prescribed an antidepressant before an adequate trial of psychotherapy was undertaken and that less than 50% were monitored for depression symptom improvement and antidepressant treatment emergent suicide related behaviours (35% and 30% respectively). Encouragingly 92% of first line prescriptions for those aged 18 years or under who were previously antidepressant-naïve was for fluoxetine as recommended. Conclusions This research has highlighted the need for targeted strategies to ensure effective implementation. These strategies might include practice system tools that allow for systematic monitoring of depression symptoms and adverse side effects, particularly suicide related behaviours. Additionally, youth specific psychotherapy that incorporates the most effective components for this age group, delivered in a youth friendly way would likely aid effective implementation of guideline recommendations for engagement in an adequate trial of psychotherapy before medication is initiated.